The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/anie.202005774
|View full text |Cite
|
Sign up to set email alerts
|

d–d Dative Bonding Between Iron and the Alkaline‐Earth Metals Calcium, Strontium, and Barium

Abstract: Double deprotonation of the diamine 1,1′‐(tBuCH2NH)‐ferrocene (1‐H2) by alkaline‐earth (Ae) or EuII metal reagents gave the complexes 1‐Ae (Ae=Mg, Ca, Sr, Ba) and 1‐Eu. 1‐Mg crystallized as a monomer while the heavier complexes crystallized as dimers. The Fe⋅⋅⋅Mg distance in 1‐Mg is too long for a bonding interaction, but short Fe⋅⋅⋅Ae distances in 1‐Ca, 1‐Sr, and 1‐Ba clearly support intramolecular Fe⋅⋅⋅Ae bonding. Further evidence for interactions is provided by a tilting of the Cp rings and the related 1H N… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 48 publications
0
17
1
Order By: Relevance
“…In these complexes, the metal–ligand bonding is contributed mainly by the metal ( n – 1)­d AOs. Calculations also suggest that the d orbitals participate in bonding in divalent species. In particular, we found that calcium is able to form heteronuclear carbonyl cation complexes with transition metals featuring a weak Fe → Ca d–d dative bond…”
Section: Heteronuclear Calcium–iron Carbonyl Cation Complexes With D–...mentioning
confidence: 82%
“…In these complexes, the metal–ligand bonding is contributed mainly by the metal ( n – 1)­d AOs. Calculations also suggest that the d orbitals participate in bonding in divalent species. In particular, we found that calcium is able to form heteronuclear carbonyl cation complexes with transition metals featuring a weak Fe → Ca d–d dative bond…”
Section: Heteronuclear Calcium–iron Carbonyl Cation Complexes With D–...mentioning
confidence: 82%
“…The strongest bonds to calcium should be covalent Ca–N bonds, which are shortened due to partial donation of the lone pairs at the nitrogen atoms to empty d orbitals of calcium. The accessibility of these orbitals in heavy alkaline earth metals has recently been demonstrated in a detailed study . The Ca–O bonds are slightly longer than typical covalent single bonds, which reflects the dative nature of this bond.…”
Section: Introductionmentioning
confidence: 84%
“…The accessibility of these orbitals in heavy alkaline earth metals has recently been demonstrated in a detailed study. 15 The Ca−O bonds are slightly longer than typical covalent single bonds, which reflects the dative nature of this bond. The short PC bonds are a hint that there might be a partial π-donation of these bonds into the d orbitals of calcium.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The geometrical optimisations followed by harmonic vibrational frequency computations of the molecules were performed at the BP86 [26] /def2‐TZVPP [27] level of theory. The BP86 functional was chosen for this project because it gave the best agreement for the geometries of the calculated molecules with experimental values and previous high‐level calculations, and it proved to be very accurate in another project in which we calculated the geometries of heavy alkaline‐earth compounds [28] . This basis set uses quasi‐relativistic effective core potentials for 28 and 46 core electrons for Sr and Ba, respectively, and all‐electron basis sets for the other atoms.…”
Section: Theoretical Methodsmentioning
confidence: 99%